Integrasi Nilai-Nilai Perilaku Anti Korupsi dalam Pembelajaran Sejarah Kebudayaan Islam di Madrasah: Reinterpretasi Tradisi Pendidikan Islam - Saiful Bahri; Ruswanto (Al-Ulum, 2024)
This study focuses on the integration of anti-corruption values in the learning of Islamic Cultural History (SKI) in madrasah. Education is seen as a strategic instrument to shape the character of the young generation with integrity, and madrasas have a crucial role in instilling Islamic moral values that are in line with anti-corruption principles. This study aims to examine the process of integration and implementation of the values of anti-corruption behavior in SKI learning in madrasah. The research method used is qualitative with multi-case and multi-site study design. Data were collected through in-depth interviews, observations, and documentation studies, and then analyzed using Miles and Huberman interactive models. The results showed that anti-corruption values have been integrated into the SKI curriculum in MI, MTs, and MA, and implemented through various contextual and participatory learning activities. Supporting factors for implementation include policy support and the relevance of Islamic values, while inhibiting factors include time and resource constraints.